PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS SMARTPHONE UNTUK MENGUPAYAKAN MINAT BELAJAR PADA PEMBELAJARAN MATEMATIKA [APPLICATION OF SMARTPHONE-BASED DISCOVERY LEARNING MODELS TO CREATE INTEREST IN LEARNING MATHEMATICS] - Purba, Joy Anwar; Dirgantoro, Kurnia Putri Sepdikasari (Universitas Pelita Harapan, 2023)
The results of the PISA study in 2018 showed that the mathematics ability of Indonesian students was still in the low performance category. One of the factors that causes this is the lack of student interest in learning mathematics. Interest is very important because it is interest that encourages students to be active and act in learning. This study aims to see whether the application of a smartphone-based discovery learning model can help increase interest in learning mathematics. The research method used is a descriptive qualitative research method using several research instruments. This research was conducted in one of the schools in South Tangerang at the junior high school level. The instruments used by the authors are observation sheets and reflection sheets and mentor feedback sheets. The results of this study concluded that the application of a smartphone-based discovery learning model is able to effect student interest in learning, which is shown by an increased willingness to learn, pleasure in learning, and student participation.BAHASA INDONESIA ABSTRACT: Hasil studi PISA pada 2018 menunjukkan kemampuan matematika siswa Indonesia masih berada dalam kategori low performance. Salah satu faktor yang menyebabkan hal ini adalah kurangnya minat siswa terhadap pembelajaran matematika. Minat menjadi hal yang sangat penting karena minatlah yang mendorong siswa untuk aktif dan bertindak dalam pembelajaran. Penelitian ini bertujuan untuk melihat penerapan model pembelajaran discovery learning berbasis smartphone dapat membantu mengupayakan minat belajar pada pembelajaran matematika. Metode penelitian yang digunakan adalah metode penelitian kualitatif deskriptif dengan menggunakan beberapa instrumen penelitian. Penelitian ini dilakukan di salah satu sekolah swasta di Tangerang Selatan pada jenjang SMP. Instrumen yang digunakan oleh penulis adalah lembar observasi, lembar refleksi, dan lembar umpan balik mentor. Penelitian ini memberikan hasil bahwa penerapan model pembelajaran discovery learning berbasis smartphone mampu mengupayakan minat belajar siswa yang ditunjukkan dengan meningkatnya kemauan untuk belajar, rasa senang siswa dan partisipasi siswa.